Students' Problem-Solving Skills Viewed from Polya's Problem Solving Indicators - Syamsudin, Annisa Febrianti; Fitriani, Andhin Dyas; Agustin, Mubiar (International Conference on Elementary Education, 2025)
Problem-solving skills are one of the essential skills that must be mastered in the 21st century, as they can develop critical thinking skills and support effective daily decision-making. Based on this, problem-solving skills need to be mastered by everyone, including elementary school students. To measure problem-solving skills, we can use the four problem-solving indicators presented by George Polya, namely understanding the problem, devising the plan, carrying out the plan, and looking back. In reality, many students have not yet mastered problem-solving skills. Therefore, this study was conducted with the aim of describing the problem-solving abilities of sixth grade elementary school students. Theresearch method used was descriptive-qualitative. The research subjects were 51 sixth-grade elementary school students. Each research subject completed a problem-solving test on the material of combined flat shapes, which consisted of eight story questions. The questions in this problem-solving test were adjusted to the problem-solving indicators according to George Polya. The results showed that 54.9% of students were able to understand the problem. As for the indicator of devising a plan, only34.3% of students possessed this skill. Then, only 17.6% of students had the skill of carrying out the plan. Last, only 12.7% of students were able to look back at the problem solution.